Short Circuit Computation At Multi Faults Situation For Solid Oxide Fuel Cell Power Generators Grid - F. BONNEYA, MEHDI; ., .; ., . (International Journal of Engineering and Technology, 2018)
Fuel cell generators takes more attention today due to its performance to operation as friendly for the environment and been one of the main sources of green energy. The subject of fuel cells has been evolved in recent years which contribute to reduce the cost of manufacturing with the increasing of durability and capacity to produce an increased amount of electrical power capacity. In this work a proposed fuel cell grid consist from ten fuel cell generators connected to a grid. As the power produced from the fuel cell is DC power, so a three-phase powerÂ invertor is connected with the fuel cell through DC link capacitor.Â Short circuit computation is performed at each bus-bar where short circuit current is calculated. Also, a proposed fault is considered at fuel cell terminal and the current at all branch of the grid is computed and the contribution current of every fuel cell generation is obtained and the bus-bar voltage at per unit value is computed. Fault current values can be used for defined the capacity of each component of the proposed grid in order to be able to confrontation high current during severe fault conditions. The program used in this work is CYME 7.1Â Â